The role of the private sector in human resource development - the Singapore experience / Ong Teong Wan - Ong, Teong Wan (1992)
In 1990, in terms of overall score, Singapore ranked top, followed by Switzerland and Japan. In 1980, it was ranked third after Switzerland and Germany. The report noted: "Singapore's edge has been its longstanding recognition that success can only come about by developing its human resources. The country realizes that government educational and training facilities will not be fully utilized without company participation in programs to upgrade skills and meet the needs of an increasingly sophisticated economy. Singapore is evolving towards a high technology industrial profile with a workforce that was based on cheap labour before the 1980s. It is essential for companies, not just the government, to offer employees the means of matching their skills with that required for operations by new investors and by established firms controlling unit costs with advanced technology."